Two-dimensional Modeling of the Tearing-mode-governed Magnetic Reconnection in the Large-scale Current Sheet above the Two-ribbon Flare. (1st August 2022) - Zhang, Yining; Ye, Jing; Mei, Zhixing; Li, Yan; Lin, Jun
Abstract: We attempt to model magnetic reconnection during the two-ribbon flare in a gravitationally stratified solar atmosphere with the Lundquist number of S = 10 6 using 2D simulations. We found that the tearing mode instability leads to inhomogeneous turbulence inside the reconnecting current sheet (CS) and invokes the fast phase of reconnection. Fast reconnection brings an extra dissipation of magnetic field which enhances the reconnection rate in an apparent way. The energy spectrum in the CS shows a power law pattern and the dynamics of plasmoids govern the associated spectral index. We noticed that the energy dissipation occurs at a scale l ko of 100–200 km, and the associated CS thickness ranges from 1500 to 2500 km, which follows the Taylor scale l T = l ko S 1/6 . The termination shock (TS) appears in the turbulent region above flare loops, which is an important contributor to heating flare loops. Substantial magnetic energy is converted into both kinetic and thermal energies via TS, and the cumulative heating rate is greater than the rate of the kinetic energy transfer. In addition, the turbulence is somehow amplified by TS, in which the amplitude is related to the local geometry of the TS.